HUBUNGAN KEBIASAAN MEMBACA JARAK DEKAT DENGAN KELAINAN REFRAKSI MIOPIA PADA SISWA SMP NEGERI 7 PADANG - Suryanta, D.I (Ensiklopedia Sosial Review, 2020)
In vision, the eye has various refractive errors. These refractive disorders include myopia, myopia is a condition in the eye that has excessive refraction power so that parallel rays that come are refracted in front of the retina. Many factors cause myopia, one of which is close reading. Reading is an activity that requires near vision. Children who read continuously for more than 30 minutes are more likely to develop myopia. This study aims to determine the relationship between the habit of reading at close range to myopia for grade IX students at SMP Negeri 7 Padang. The results showed that there was a relationship between history of close reading and myopia. Where Ho is rejected and H1 is accepted, while the strength between variables in this study is assessed using adds ratio. The OR calculation result is 0.405 because OR (0.405)